INVESTIGATING HOW PERCEIVED BENEFIT, EASE OF USE, AND RISK AFFECT FINTECH USAGE ADOPTION - Wijaya, Henryanto; Firdausy, Carunia Mulya; Widjaja, Indra (Graduate Program of Universitas Tarumanagara, 2025)
This research aims to investigate the impact of perceived benefits, perceived ease of use, and perceived risks on Fintech usage adoption among Fintech users in Indonesia. This study employs a quantitative analysis method using primary data collected through questionnaires. The sample size was obtained through non-probability sampling, consisting of 246 Fintech service users. The data analysis method used partial least squares-structural modeling (PLS-SEM) with Smart PLS 4.0 application. The research findings indicate that perceived benefits and perceived ease of use have a positive and significant impact on Fintech usage adoption among Fintech users. On the other hand, perceived risk shows a positive but non-significant impact on the Fintech user adoption. Therefore, perceived benefits and perceived ease of use are crucial and must be considered in supporting Fintech usage adoption among Fintech users.